TRANSFORMASI PEMBELAJARAN INTERAKTIF BERBASIS CANVA DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SDI PABAENG-BAENG - Rafiah Tuzsaliha; Indra; Aliem Bahri; Muhammad Muzaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to examine the improvement in student learning outcomes at SDI Pabaeng-Baeng through the use of Canva as an interactive medium in the learning process. Employing Classroom Action Research (CAR) with the Kurt Lewin model, the research follows the phases of planning, action, observation, and reflection. The study involved 27 third-grade students from class 3 Baji Pamaik at SDI Pabaeng-Baeng, Makassar City. Data were collected using pretest and post-test instruments, which were then analyzed descriptively. The results show that incorporating Canva as an interactive medium in Indonesian language learning positively impacted student learning outcomes. This is evidenced by an increase in completion rates, from 37% (10 students) in the pre-cycle to 56% (15 students) in the first cycle, and significantly rising to 81% (22 students) in the second cycle.